Improving water quality in Nile tilapia culture using a multi-stage filtration system - Surakusumah, Wahyu; Kusumawaty, Diah; Dewina, Restu Utari; Belva, Aisyah; Oktavia, Fadya; Qanita, Kirey; Nurfarida, Naneu; Nabila, Siti (Jurnal Abmas, 2026)
Algal bloom in Nile tilapia (Oreochromis niloticus) culture systems based on Recirculating Aquaculture Systems (RAS) can degrade water quality and increase the risk of fish stress. This community service program aimed to implement a multi-stage filtration system as an eco-friendly and energy-efficient solution to control microalgae growth and improve water quality in Nile tilapia culture ponds. The program was conducted through a Biology Study Program consultancy project involving lecturers, students, and the Padasuka Nila Cimahi aquaculture partner. The filtration system combined mechanical and biological filtration using fishing nets, gravel, kaldness K1, filter brushes, coral stones, and zeolite. Water quality parameters, including pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), and total ammonia, were evaluated before and after system implementation. The results showed that the filtration system reduced pH from 9.18 to 7.60, EC from 284 µS/cm to 212 µS/cm, TDS from 147 ppm to 115 ppm, and total ammonia from 0.5 mg/L to 0.18 mg/L. In addition, pond water became visually clearer, and microalgae growth decreased significantly. The multi-stage filtration system proved to be an effective, low-cost, and sustainable approach for improving water quality in small- to medium-scale Nile tilapia aquaculture systems.